The Defense Lawyer : The Barry Slotnick Story - Patterson, James, 1947-; Wallace, Benjamin, 1968- (New York : Little, Brown and Company, 2021)
Bronx-native Bernard Slotnick's mantra was that everyone deserved a good defense--and he was the best defender out there. A bold strategist in the courtroom, and a doting husband and father of four at home, "Liberty's Last Champion" stood up for the unpopular and the controversial, including John Gotti, head of the Gambino crime family; Joe Colombo Sr., inspiration for The Godfather; Rabbi Meir Kahane, founder of the Jewish Defense League; and Bernhard Goetz, the Subway Shooter. Known for his sharp mind (and his sharp suits), Slotnick had twelve-year winning streak, and James Patterson tells his story here.
Keywords: Slotnick, Barry, -- 1939-; Criminal defense lawyers -- Biography -- United States; Lawyers -- Biography -- United States; Biographies